Cynaropicrin Shows Antitumor Progression Potential in Colorectal Cancer Through Mediation of the LIFR/STATs Axis - Zheng, Dandan; Zhu, Yu; Shen, Yili; Xiao, Sisi; Yang, Lehe; Xiang, Youqun; Dai, Xuanxuan; Hu, Wanle; Zhou, Bin; Liu, Zhiguo; Zhao, Haiyang; Zhao, Chengguang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Colorectal cancer (CRC) is the second deadliest malignant disease in the world and the leukemia inhibitory factor receptor/signal transducers and activators of transcriptions (LIFR/STATs) signaling axis plays an important role in the molecular biology of CRC. Methods: Cell function tests were performed to observe the inhibitory effect of Cynaropicrin on human CRC cells (RKO, HCT116 and DLD1). Expression levels of LIFR, P-STAT3, P-STAT4 and apoptotic proteins were detected by Western blotting. Immunoprecipitation confirmed the presence of LIFR/STAT3/STAT4 complex. Cell immunofluorescence assay was used to observe the subcellular localization of STAT3 and STAT4. In vivo efficacy of Cynaropicrin was evaluated by a xenotransplantation model in nude mice. Results: Cynaropicrin significantly reduced the survival ability of human CRC cells and promoted apoptosis in a dose-dependent manner. Western blotting results suggested that the antitumor effects of cynaropicrin might be mediated by inhibition of the LIFR/STATs axis. Cynaropicrin reduced the formation of STAT3/STAT4 heterodimers and blocked their entry into the nucleus. Cynaropicrin also suppressed tumor growth in the xenograft model. Conclusion: The results showed that cynaropicrin exerted a strong inhibitory effect on CRC in vitro and in vivo. Our study concluded that cynaropicrin has potential application prospects in the field of anti-CRC therapy.